Simulation and Test Study of Transmission Rattle Sensitivity - Lü Pin; Xiaoqiang Zhou; Junfeng Hu; Xiaolong Deng; Jun Lan; Tianbao Tang (Jixie chuandong)
Taking a DCT transmission preliminary gear 3 to 2 as an example，through the analysis of rattle theory and influence factors，the precise comparison verification result between simulation and test of rattle sensitivity are obtained. The quantitative evaluation target of rattle sensitivity is formulated，and different flywheels are matched for real vehicle verification. This research has theoretical significance and practical value for guiding low-noise design and matching engine platform of transmission.